Cigarette smoking is associated with adverse survival among women with ovarian cancer: Results from a pooled analysis of 19 studies. Issue 11 (24th January 2017) - Præstegaard, Camilla; Jensen, Allan; Jensen, Signe M.; Nielsen, Thor S. S.; Webb, Penelope M.; Nagle, Christina M.; DeFazio, Anna; ,; Høgdall, Estrid; Rossing, Mary Anne; Doherty, Jennifer A.; Wicklund, Kristine G.; et al.
Abstract : Cigarette smoking is associated with an increased risk of developing mucinous ovarian tumors but whether it is associated with ovarian cancer survival overall or for the different histotypes is unestablished. Furthermore, it is unknown whether the association between cigarette smoking and survival differs according to strata of ovarian cancer stage at diagnosis. In a large pooled analysis, we evaluated the association between various measures of cigarette smoking and survival among women with epithelial ovarian cancer. We obtained data from 19 case‐control studies in the Ovarian Cancer Association Consortium (OCAC), including 9, 114 women diagnosed with ovarian cancer. Cox regression models were used to estimate adjusted study‐specific hazard ratios (HRs), which were combined into pooled hazard ratios (pHR) with corresponding 95% confidence intervals (CIs) under random effects models. Overall, 5, 149 (57%) women died during a median follow‐up period of 7.0 years. Among women diagnosed with ovarian cancer, both current (pHR = 1.17, 95% CI: 1.08–1.28) and former smokers (pHR = 1.10, 95% CI: 1.02–1.18) had worse survival compared with never smoking women. In histotype‐stratified analyses, associations were observed for mucinous (current smoking: pHR = 1.91, 95% CI: 1.01–3.65) and serous histotypes (current smoking: pHR = 1.11, 95% CI: 1.00–1.23; former smoking: pHR = 1.12, 95% CI: 1.04–1.20). Further, our results suggested that current smoking has a greater impact on survival among women with localized than disseminated disease. The identification of cigarette smoking as a modifiable factor associated with survival has potential clinical importance as a focus area to improve ovarian cancer prognosis. Abstract : What's new? The number of female smokers is declining worldwide but an estimated 180 million women still smoke daily worldwide. Here the authors examined the association between cigarette smoking and ovarian cancer survival. Current and former smoking shortened survival compared to women who had never smoked, especially in those afflicted with mucinous and serous tumors and with localized disease. The study identifies cigarette smoking as a modifiable factor associated with ovarian cancer survival.